Developing Chinese university students’ academic literacies in English language classrooms via a production-oriented approach: an action research perspective - Yajuan Gao; Hao Wang (Frontiers in Psychology, 2023)
Developing academic literacies is becoming an important research topic in TESOL and has received increasing scholarly attention. One of the difficulties in developing university students’ academic literacy in English language speaking is the lack of an authentic English language learning environment and the way to help students more effectively develop their language competence. To address this issue, this study seeks to explore the academic literacy development of 24 non-English major students in an 8-week-long integrated English class at a Chinese university from late 2022 to early 2023. Based on a production-oriented approach (POA) action research design, this study follows the typical framework of driving, enabling, and assessing phases to chain together the teaching and learning actions. Quantitative data from questionnaires were analyzed via SPSS software, whereas thematic analysis and content analysis were adopted in examining the qualitative data including classroom observations, teacher reflection journals, and semi-structured interviews. Based on our data analysis, this study finds that POA can have a positive effect on improving students’ participation, performance, and task completion, which improves their academic literacies. Implications on how POA helps in facilitating EFL students’ academic literacies development are discussed along with the acquisition model and future research directions like students’ identity issues and teachers’ perceptions of pedagogical approaches in teaching academic literacy within university settings.